RELATIONSHIP OF ADDITIONAL NUTRITIONAL CONSUMPTION OF GREEN BEANS (VIGNA RADIATA) WITH BREAST MILK PRODUCTION. - Rohmi Handayani; Siti Yulaikah (Journal of Midwifery, 2020)
Background: The protein needed by breastfeeding mothers can be supplied from nuts, including green beans. Green beans contain active compounds, namely polyphenols and flavonoids which function to increase the hormone prolactin. When the prolactin hormone increases, milk secretion will be maximized so that the quantity of breast milk will increase and the nutritional content contained in green beans will increase the nutritional content in breast milk (Suskesty, 2017)Purpose of the study: to determine the relationship between the frequency of breastfeeding and the provision of additional nutritional consumption of vigna radiate with milk production in post-partum mothers on the 15th day in Klaten district.Methods: This type of research is pre-experimental design with post test only design with control group design. The population in this study were all mothers who had babies aged 1-3 months and resided in the working area of Puskesmas Klaten from January to September 2020. This study is a mother who has a baby aged 1 - 3 months and breastfeeding exclusively in the working area of Puskesmas Klaten with a sample size of 40 respondents consisting of 20 respondents in the treatment group (consumption of green beans) and 20 respondents in the control group (not consuming green beans). . The data analysis technique is the Spearman Correlation and Independent T-Test.Results: There was a correlation between the frequency of breastfeeding and milk production on the 15th day of postpartum mothers with a P value: .000. There is a difference in the average milk production in the 15th day postpartum mothers who are given additional Vigna Radiata (green beans) food and not given Vigna Radiata with P value: .000Conclusion: The frequency and consumption of additional Vigna radiata (green beans) nutrition can increase breast milk production